1996
DOI: 10.1182/blood.v88.1.289.289
|View full text |Cite
|
Sign up to set email alerts
|

Clonal circulating cells are common in plasma cell proliferative disorders: a comparison of monoclonal gammopathy of undetermined significance, smoldering multiple myeloma, and active myeloma

Abstract: The blood of most patients with active multiple myeloma (MM) contains cells related to the bone marrow tumor. However, identifying clonal cells in the blood of patients with monoclonal gammopathy of undetermined significance (MGUS) has been difficult. In this study, we analyzed blood mononuclear cells (BMNCs) from 16 patients with MGUS, 2 with amyloidosis, 8 with smoldering MM (SMM), 2 with indolent MM (IMM), and 15 with active MM using three different methods to detect and quantitate clonal cells, ie, immunof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(28 citation statements)
references
References 0 publications
2
25
1
Order By: Relevance
“…In these cases, ASO-PCR provided no increase in sensitivity over either IgH-PCR or flow cytometry. The results of Billadeau et al (1996) indicated that approximately 70% of patients with circulating clone will have levels within the sensitivity of the flow cytometric assay. We would therefore suggest that it is more rapid and cost-effective to assess these samples with flow cytometry and/or consensus primer-PCR first, in order to determine whether there is a requirement to develop patient-specific primers.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, ASO-PCR provided no increase in sensitivity over either IgH-PCR or flow cytometry. The results of Billadeau et al (1996) indicated that approximately 70% of patients with circulating clone will have levels within the sensitivity of the flow cytometric assay. We would therefore suggest that it is more rapid and cost-effective to assess these samples with flow cytometry and/or consensus primer-PCR first, in order to determine whether there is a requirement to develop patient-specific primers.…”
Section: Discussionmentioning
confidence: 99%
“…Some circulating B lymphocytes (CD19 + ) in MGUS and MM also carry karyotypic changes and chromosomal aberrations similar to myeloma cells. About 0AE1-1AE8% (MM) and 0.02% (MGUS) of CD19 + circulating cells carry similar chromosomal changes as BM myeloma cells (Chen & Epstein, 1996;Billadeau et al, 1996;Zojer et al, 2001).…”
Section: Circulating Clonal Cells In Mgus and MMmentioning
confidence: 99%
“…Multiple myeloma (MM) is a malignant disease that results from the uncontrolled proliferation of plasma cells derived from a single clone (Billadeau et al , 1996). The most common clinical problem in patients with MM is extensive bone destruction (or bone resorption), which occurs in almost all patients and is accompanied by severe and intractable pain and susceptibility to fracture (Roodman, 1997).…”
mentioning
confidence: 99%